EFFECT OF BRUTO REGIONAL DOMESTIC PRODUCTS AND REGIONAL EXPENDITURE AGAINST POVERTY IN DISTRICT / NORTH SUMATERA CITY 2014-2016 - Winda Suheini Zahwa Ritonga; Asnawi Asnawi (LPPM Universitas Malikussaleh, 2018)
The purpose of this study is to determine the effect of Gross Regional Domestic Products(GRDP) and Government Expenditure on Poverty in the District / City of North Sumatra in 2014-2016. This study uses a panel data obtained from the Central Bureau of Statistics. The data analysis method used in this study is a panel data regression analysis method with Random Effect Model. The results show that GRDP has a positive influence on poverty, while Government Expenditures do not affect poverty.